PEMANFAATAN LIMBAH KULIT SINGKONG (Manihot Utilissima) DALAM MEMPENGARUHI KADAR FE DALAM AIR - Yusriani Sapta Dewi; Dwi yono (FT-USNI, 2017)
This study aims to design a waste water treatment plant (WWTP) design; reference in making WWTP in another place; and do waste water treatment so it is not harmful to the surrounding environment. The location of the research in the Jakarta Transmart building, when this research was conducted in March to June 2018. The method used in the implementation of this study planning was the preparation of reports that included analysis of waste characteristics; review of literature studies that are used to study supporting theories during conducting problem analysis and discussion so that they can be considered into the planning of wastewater treatment institu- tions that will be carried out; collection of primary data and secondary data as material for study of wastewater treatment plant planning; and design, calculation of the dimensions of the wastewater treatment plant, technical specifications. Planning criteria, among others: processing efficiency and achieving target results in accordance with desired quality standards; land area needed; and care must be easy and simple. The results showed that the estimated discharge of water requirements found in the Transmart building was around 59.97 m³ / day, obtained from the calculation of the area of the building building to meet the needs of clean water needed per square meter. Aeration tank volume and Aeration 1 dimensions: 3.35 m long, 4.450 m wide, 2.550 m depth, 0.625 m free space height, 38.01 m³ volume. Aeration 2: 3.375 m long, 4.450 m wide, 2.550 m depth, 0.625 m free space height, 38.3 m³ volume. Total aeration body area = 76,315 m. Tub sedimentation: 3.35 m long, 2.850 m wide, 2.350 m depth, 0.90 m free space height, 38.3 m³ volume. Volume: 13.7. Tub Equalization: 2.625 m long, 5.975 m wide, 2.60 m depth, free space height 0.575 m, volume 40 m³. In the design of planning the installation of wastewater treatment systems for activated sludge should be added or further processing so that the water from processing can be reused and not wasted, such as filtration so that it can be used such as for washing vehicles, watering plants etc.